The Effect Wadi Alshati Iron Oxide Fine-Particles on the compressive Strength of the Concrete - Mohammed Al Kilani Almadani & Ibrahim Bakari Al-Arabi (Journal of Pure & Applied Sciences, 2019)
Concrete is a heterogeneous material obtained by mixing cement paste (binder) with aggregates (filler), the later constituting more than 80% of the concrete. Concrete is a macro-material strongly influenced by addition of fine-properties such as iron oxide. One of the most important properties of hardened concrete is its compressive strength, which can be quantitatively measured. The objective of the present work is to study the effect of partial replacement of one of (Wadi Alshati) iron oxide fine-particles. Its proposed to replace fine aggregates with iron oxide and find its effects on the compression strength of the concrete. Six percentage levels of replacement i.e. 5, 10. 15, 20, 25 and 30 percent are considered for partially replacing sand with iron oxide. Plain concrete (PC) grade is initially designed without replacement and subsequently sand is partially replaced with iron oxide. The compressive strength was measured after 14 days of completion of curing. Results showed that the compressive strength of the concrete using iron oxide nanoparticles were not equivalent to that of the conventional concrete. Maximum decreasing in compressive strength was about 40%. According to the results of compression strength for conventional and incorporated specimen, the addition of iron oxide to concrete will decreases the compressive strength of concrete due to formation of porosity.